Investigating the critical role of Hormuud’s EVC-Plus mobile money in augmenting the delivery of lifesaving humanitarian aid in Somalia - Nor, Mohamed Ibrahim (Frontiers in Human Dynamics, 2026)
This study investigates the pivotal role of Hormuud Telecom’s EVC-Plus mobile money platform in enhancing the delivery of lifesaving humanitarian aid in Somalia, one of the world’s most fragile states. It examines how operational accessibility, financial integration, and inclusive financial resilience influence the effectiveness of humanitarian aid programs in contexts of systemic fragility. A quantitative survey design was employed, drawing on data from 240 respondents, including humanitarian practitioners, beneficiaries, and mobile money users. Anchored in Diffusion of Innovation Theory, Financial Inclusion Theory, and the Resource-Based View (RBV), this study utilized multiple regression analysis to assess both direct effects and interaction dynamics among core variables. Model diagnostics ensured reliability, validity, and robustness. The results demonstrate that financial integration, usability and accessibility, and inclusive financial resilience significantly improve the effectiveness of humanitarian aid delivery. Among these factors, financial integration emerged as the strongest predictor. However, the interaction effect between operational accessibility and financial integration was significantly negative, suggesting diminishing returns when both dimensions are simultaneously maximized. These findings position EVC-Plus as a critical humanitarian infrastructure while highlighting the need for balanced integration strategies. The study provides actionable insights for humanitarian organizations, policymakers, and mobile money providers. It advocates for inclusive program design, capacity building for digital literacy, and collaborative partnerships to enhance service reach and efficiency. For policymakers, the results underscore the importance of integrating mobile money platforms into national social protection and emergency response frameworks, supported by robust regulatory safeguards and investments in digital infrastructure. This study is among the first empirical investigations to position mobile money platforms as strategic humanitarian infrastructures rather than mere financial tools in fragile state contexts. Linking digital financial services with humanitarian aid delivery provides a novel framework for understanding the systemic role of mobile money in crisis response. This research enriches the fields of humanitarian finance, digital inclusion, and mobile money adoption by offering empirical evidence from Somalia’s unique context. It extends theoretical frameworks by demonstrating how EVC-Plus bridges technological innovation, institutional resilience, and inclusive development, offering a scalable model for fragile and conflict-affected states.